Behavioral profiles displayed by rats in an elevated asymmetric plus-maze: effects of diazepam - Ruarte,M.B. (1999)
When rats are exposed to unknown environments where novelty and fear-inducing characteristics are present (conflictive environments), some specific behaviors are induced and exploration is apparently modulated by fear. In our laboratory, a new type of plus-maze was designed as a model of conflictive exploration. The maze is composed of four arms with different geometrical characteristics, differing from each other by the presence or absence of walls. The degree of asymmetry was as follows: NW, no wall arm; SW, a single high wall present; HL, a low and a high wall present, and HH, two high walls present. The four arms were arranged at 90o angles and the apparatus was called the elevated asymmetric plus-maze (APM). The purpose of the present study was to assess the behavioral profile of rats exposed for a single time to the APM with or without treatment with benzodiazepine. Increasing doses of diazepam were injected intraperitoneally in several groups of male, 90-day-old Holtzman rats. Distilled water was injected in control animals. Thirty minutes after treatment all rats were exposed singly to a 5-min test in the APM. Diazepam induced a biphasic modification of exploration in the NW and SW arms. The increase in the exploration score was evident at low doses of diazepam (0.25-1.0 mg/kg body weight) and the decrease in exploration was found with the higher doses of diazepam (2.0-3.0 mg/kg body weight). Non-exploratory behaviors (permanency) were not affected by benzodiazepine treatment. In the HL arm, exploration was not modified but permanency was increased in a dose-dependent manner. In the HH arm, exploration and permanency were not affected. Results are compatible with the idea that exploration-processing mechanisms in conflictive environments are modulated by fear-processing mechanisms of the brain.